The interest of the neighbourhood: Where municipal councillors live within the Brussels Capital Region - Filip de Maesschalck (Brussels Studies, 2009)
This article examines the extent to which certain types of neighbourhood are underrepresented or overrepresented in the Brussels municipal councils. It is found that as the prosperity of a neighbourhood increases, so does its representation. Neighbourhoods in difficulty therefore suffer from a double form of deprivation as not only do they accumulate a number of urban problems, but they are also underrepresented within municipal bodies. There are also significant differences between the political ideologies that can be linked to their position within the political spectrum. A comparison with the previous legislature indicates a stable picture. However, the increasing number of municipal councillors of non-European origin is leading to better representation of neighbourhoods that accumulate the most problems, even though they are still underrepresented. The same observations are made for the Brussels Parliament, albeit that the representation of prosperous neighbourhoods is even higher there.